2003
DOI: 10.1177/089686080302300206
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Teicoplanin in Patients Undergoing Continuous Ambulatory Peritoneal Dialysis

Abstract: Objective To achieve concentrations of teicoplanin in serum and dialysate within the therapeutic range in patients undergoing continuous ambulatory peritoneal dialysis (CAPD). Design Pharmacokinetic study. Setting A tertiary-care hospital. Patients Eight hospitalized anuric patients undergoing CAPD. Interventions One single dose of 10 mg/kg teicoplanin was administered intravenously, and blood and dialysate were sampled at regular time intervals for 48 hours post drug infusion. Concentrations of teicoplanin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Furthermore, the minimum inhibitory concentration (MIC) of vancomycin appears to be shifting upwards in some institutions, a phenomenon known as MIC creep; and, where the MIC increase occurs, treatment failure is common[ 53 , 54 ]. Teicoplanin MIC creep has also been described; but, regardless, when it is administered intravenously it does not achieve therapeutic concentration in the ascitic fluid[ 55 ].…”
Section: Current Therapeutic Strategies For Sbp By Gpbmentioning
confidence: 99%
“…Furthermore, the minimum inhibitory concentration (MIC) of vancomycin appears to be shifting upwards in some institutions, a phenomenon known as MIC creep; and, where the MIC increase occurs, treatment failure is common[ 53 , 54 ]. Teicoplanin MIC creep has also been described; but, regardless, when it is administered intravenously it does not achieve therapeutic concentration in the ascitic fluid[ 55 ].…”
Section: Current Therapeutic Strategies For Sbp By Gpbmentioning
confidence: 99%
“…On the other hand, when teicoplanin was administered intravenously (IV) at 10 mg/kg of body weight, low concentrations were achieved in peritoneal fluid. (18) Linezolid cannot be used in the majority of patients with cirrhosis and bacterial infections because of thrombocytopenia. Daptomycin is a lipopeptide that is highly effective against MDR Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci.…”
mentioning
confidence: 99%
“…As for glycopeptides, there are some concerns owing to a high rate of vancomycin‐resistant Enterococci in patients with cirrhosis and nosocomial infections and the potential risk of nephrotoxicity. On the other hand, when teicoplanin was administered intravenously (IV) at 10 mg/kg of body weight, low concentrations were achieved in peritoneal fluid . Linezolid cannot be used in the majority of patients with cirrhosis and bacterial infections because of thrombocytopenia.…”
mentioning
confidence: 99%
“…Currently, glycopeptides, which for years have been the chief antibiotic for MDR Gram-positive cocci infections, give concerns owing to a high rate of vancomycin-resistant enterococci (VRE), the potential risk of nephrotoxicity and an increase in the mean minimum inhibitory concentration (MIC) of vancomycin in clinical isolates (a phenomenon known as MIC creep), besides when teicoplanin is administered intravenously at 10 mg/kg of body weight, low concentrations are achieved in peritoneal fluid (5). These observations seem to be confirmed by the Randomized Clinical Trial of Piano et al (2), who demonstrated high efficacy of daptomycin combined to meropenem for the treatment of N-SBP.…”
Section: Nosocomial Spontaneous Bacterial Peritonitis: Discussing a Smentioning
confidence: 99%